Solidarność jako propozycja przezwyciężenia kryzysu w Unii Europejskiej - Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The most serious consequence of adopting the power-politics model is a constant increase in imbalanced cost and benefit distribution arising from European integration. It entails shifting costs from the most influential states to the weakest ones, which de facto destroys the principle of solidarity.Solidarity, defined by J. Habermas as ‘another side of justice’ and which assumes that another person is not only an equal but also a unique entity, is a necessary condition for discourse. The institutionalsafeguard is a reasonably agreed law based on the agreement of all the cooperating parties who believe in Habermas’s constitutional patriotism expressing citizens’ solidarity. A new form of solidarity is a constructivist community. It is related to Durkheim’s thought about social developmentfrom mechanical solidarity which deals with sharing common beliefs and standards to organic solidarity which depends on differences between people and their mutual needs to complement each other within various unions and communities. This type of solidarity requires all members’ cooperationto approve of the agreed values. Therefore, social integration takes place through cooperation, whereas its aim is to improve rationality. An inclusive community is also a cooperation community.
Keywords: Unia Europejska; solidarność; kryzys; Habemas, Jürgen (1929-); Durkheim, Émile (1858-1917)